Assessment of heavy metals in soil and water from Bahi district, Tanzania - Dominic Parmena Sumary; Jofrey Raymond; Musa Chacha; Firmi Paul Banzi; Edwin Gomezulu (PLoS ONE, 2025)
This study presents analysis of heavy metals concentrations in soil and water samples collected from villages near Bahi Swamp found in Bahi district, Tanzania. The research involved quantitative analyses methods of heavy metals in the laboratory and the use of descriptive statistical methods to draw conclusion. A total of 45 soil samples and 21 water samples were collected from five locations near Bahi Swamp which was pre-selected from northern and the eastern part. Heavy metals from soil and water samples were analyzed by using energy dispersive X-ray fluorescence (ED-XRF) spectrometry and atomic absorption spectrometry (AAS) technique, respectively. The concentrations of nine heavy metals (Pb, Cd, Mn, Zr, Cu, As, Zn, Sr, Cs) in soil samples and three in water samples (Mn, Zn, Cu) were determined. The mean concentrations of heavy metal from soil samples were Pb (29.60 ± 7.50 mg kg-1), Cd (403.20 ± 507.44 mg kg-1), Mn (478.27 ± 245.86 mg kg-1), Zr (206.00 ± 79.47 mg kg-1), Cu (52.00 ± 5.24 mg kg-1), As (5.27 ± 1.66 mg kg-1), Zn (48.47 ± 31.18 mg kg-1), Sr (21.93 ± 36.99 mg kg-1), and Cs (34.00 ± 10.95 mg kg-1). Soil samples exhibited diverse trace element patterns, with concentrations following the order As <Pb < Zn < Cu < Sr < Cs < Zr < Cd < Mn. Notably, Cd concentrations in Bahi Sokoni (BSS) and Bahi Matajila (BTS) exceeded other locations by over 20 times of the concentrations ranged from 38 to1157 mg kg-1. Manganese (Mn) concentrations varied significantly, but were still within the permissible limits set by regulatory authorities such as, FAO/WHO, US EPA and TBS. Also, the study of metal oxides found that the mean concentration of tellurium oxide (TeO2) in soil samples was significantly higher than typical natural abundance levels. Water samples displayed a wide range of Mn concentrations, while Zn was detected in specific sites. Thus, the findings pose a potential health and environmental concerns, serving as contribution for further research and highlighting environmental regulatory compliance with an emphasis that Bahi is known for its uranium deposits.